2014
DOI: 10.1371/journal.pone.0091876
|View full text |Cite
|
Sign up to set email alerts
|

Early Fish Myoseptal Cells: Insights from the Trout and Relationships with Amniote Axial Tenocytes

Abstract: The trunk muscle in fish is organized as longitudinal series of myomeres which are separated by sheets of connective tissue called myoseptum to which myofibers attach. In this study we show in the trout that the myoseptum separating two somites is initially acellular and composed of matricial components such as fibronectin, laminin and collagen I. However, myoseptal cells forming a continuum with skeletogenic cells surrounding axial structures are observed between adjacent myotomes after the completion of somi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 44 publications
(63 reference statements)
2
32
0
1
Order By: Relevance
“…It has been shown that the dermomyotome-like epithelium provides muscle progenitors necessary for myotome growth, (Hollway et al, 2007;Stellabotte et al, 2007;Steinbacher et al, 2008) and, in line with their myogenic commitment, cells of the dermomyotome-like epithelium express the myogenic markers Pax3 and Pax7 as shown in zebrafish (Groves et al, 2005;Devoto et al, 2006;Hammond et al, 2007) and trout (Dumont et al, 2008). Our observation that the dermomyotome-like epithelium expresses CILP1 in addition to collagen I, V and XII (Bricard et al, 2014) further supports the view that this epithelium not only is myogenic, but also has a major role in the formation of the acellular connective tissue between the myotome and the epidermis. Whether this epithelium, which notably expresses dermo-1, a marker of dermis differentiation (Dumont et al, 2008), actually gives rise to cells of the dermis is still debated (Hollway et al, 2007; Stellabote et al, 2007).…”
Section: Ralliere Et Alsupporting
confidence: 73%
See 4 more Smart Citations
“…It has been shown that the dermomyotome-like epithelium provides muscle progenitors necessary for myotome growth, (Hollway et al, 2007;Stellabotte et al, 2007;Steinbacher et al, 2008) and, in line with their myogenic commitment, cells of the dermomyotome-like epithelium express the myogenic markers Pax3 and Pax7 as shown in zebrafish (Groves et al, 2005;Devoto et al, 2006;Hammond et al, 2007) and trout (Dumont et al, 2008). Our observation that the dermomyotome-like epithelium expresses CILP1 in addition to collagen I, V and XII (Bricard et al, 2014) further supports the view that this epithelium not only is myogenic, but also has a major role in the formation of the acellular connective tissue between the myotome and the epidermis. Whether this epithelium, which notably expresses dermo-1, a marker of dermis differentiation (Dumont et al, 2008), actually gives rise to cells of the dermis is still debated (Hollway et al, 2007; Stellabote et al, 2007).…”
Section: Ralliere Et Alsupporting
confidence: 73%
“…Skeletogenic cells surrounding the notochord have been shown to originate from the sclerotome compartment ventral to the myotome (Morin-Kensicki and Eisen, 1997). Although awaiting definitive evidence, it is likely that myoseptal/tendon cells originate from a sclerotome derivedcompartment similar to the syndetome of the amniotes (Bricard et al, 2014;Chen and Galloway, 2014;Subramanian and Schilling, 2014). Thus, although myoseptal and skeletogenic cells are likely to share a common sclerotomal origin, they rapidly differ not only by the expression of scleraxis and Osf2/periostin as previously reported (Bricard et al, 2014) but also by that of CILP1.…”
Section: Fig 3 (Above Right) Embryonic Expression Of Cilp1 In the Tmentioning
confidence: 55%
See 3 more Smart Citations